Transformation of flexural waves on the vertical boundary in a stepwise waveguide - Gorodetska, N. S.; Nedil’ko, O. O. (Reports of the National Academy of Sciences of Ukraine, 2014)
The estimation of the diffraction of Rayleigh–Lamb's waves on the vertical boundary of a waveguide formed by the strong contact of two half-strips with identical mechanical properties and different heights has been obtained on the basis of the superposition method. The analysis of the energy transformation of the incident wave into reflected and transmitted waves depending on the frequency at the different ratios of the heights of the contacting layers has been performed.